Comparing Different Switching Techniques For Silicon Carbide MOSFET Assisted Silicon IGBT Based Hybrid Switch - Ozdemir, Sadik; Acar, Fatih; Selamogullari, Ugur S. (IEEE, 2015)
This study compares different switching techniques for Silicon Carbide (SiC) MOSFET assisted Silicon (Si) IGBT based hybrid switch and presents the effect of hybrid switch control techniques on the efficiency improvement. The hybrid switch which parallels a IGBT with a SiC MOSFET is proposed as a solution to improve the light load efficiency. The hybrid switch combines desirable properties both IGBT and SiC MOSFET. Different operation modes of hybrid switch are analyzed in PSIM using a simple circuit and it is shown that the hybrid switch performs better compared to IGBT alone operation.
Keywords: Light load efficiency; hybrid switch; synchronous rectification; INVERTER; Computer Science; Engineering